2015
DOI: 10.1080/00140139.2015.1057543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sports bra type and gait speed on breast discomfort, bra discomfort and perceived breast movement in Chinese women

Abstract: The compression sports bra provided more comfortable support than the encapsulation sports bra for these Chinese women when running on a treadmill. However, these women perceived higher bra discomfort when wearing the compression bra when stationary. Further research is needed to modify the design of sports bras, particularly the straps, to provide adequate and comfortable breast support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ placement 41 , and fabric and thermal properties 42,43 . Women who ran on a treadmill while wearing a high support sports bra rated their experience as more comfortable with less pain than while wearing a low support bra 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports www.nature.com/scientificreports/ placement 41 , and fabric and thermal properties 42,43 . Women who ran on a treadmill while wearing a high support sports bra rated their experience as more comfortable with less pain than while wearing a low support bra 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Women who ran on a treadmill while wearing a high support sports bra rated their experience as more comfortable with less pain than while wearing a low support bra 39 . The bra strap contributes to the most overall discomfort during exercise 41 , and a cross-strap design with cushioning may help to reduce the distress 40 . As technology to measure biometric data such as heart rate is introduced to the sports bra garment, manufacturers should carefully consider design elements.…”
Section: Discussionmentioning
confidence: 99%
“…Breasts were found to move in a three-dimensional sinusoidal pattern relative to the torso, with increased "breast bounce" (displacement) being associated with increased breast pain (64). Numerous biomechanical studies have since confirmed this sinusoidal breast movement pattern, with greater breast displacement found with increased breast mass, vertical torso motion, and lower limb cadence (22,86,97,142,144,164). Conversely, less breast displacement was found when women wore increased external breast support, usually provided by a sports bra (22,51,77,82,84,89,101,116,120,133,143,160,164,166,175,176).…”
Section: How Does the Breast Move?mentioning
confidence: 90%
“…Numerous biomechanical studies have since confirmed this sinusoidal breast movement pattern, with greater breast displacement found with increased breast mass, vertical torso motion, and lower limb cadence (22,86,97,142,144,164). Conversely, less breast displacement was found when women wore increased external breast support, usually provided by a sports bra (22,51,77,82,84,89,101,116,120,133,143,160,164,166,175,176). Graphs of three-dimensional breast displacement during treadmill running, when women ran with and without breast support, are displayed in Scurr et al (144).…”
Section: How Does the Breast Move?mentioning
confidence: 91%
“…An appropriate range of clothing pressure can improve clothing fit and, thus, facilitate physical activity. It does not only improve work efficiency but also helps to maintain and promote health [ 18 , 19 , 20 ]. On the other hand, excessively high clothing pressure may cause indigestion or duodenitis by altering the location and form of the body’s organs.…”
Section: Introductionmentioning
confidence: 99%